Transgenic mice ubiquitously expressing human Fas ligand develop a slight form of graft-versus-host-like disease - Ma Ying-Hua; Fei Jian; Hu Jia-Hua; Zhou Xiao-Gang; Xia Guo-Hong; Guo Li-He (Acta Pharmacologica Sinica; Vol 22, No 4 (Apri 2001): Acta Pharmacologica Sinica, 2016)
Aim: To construct transgenic mice bearing human Fas ligand (FasL/CD95L) cDNA, and further explore the physiological effects of ubiquitous expression of FasL on such animals. Methods: Transgenic mice were produced by pronuclei microinjection method. Integration and transmission of transgene were identified by nest-PCR and Southern-blot analysis. Level of FasL mRNA was evaluated by semi-quantitative RT-PCR analysis. FasL protein was detected by immunofluorescence analysis. Morphological alterations in tissues were analyzed by histological examination. The percentage of alphabetaT cells in the spleen was determined by flow cytometry analysis. Results: Two independent founder mice bearing human FasL cDNA under the control of CMV promoter were generated healthily. Human FasL was moderately expressed in the majority of tissues examined in F1 heterozygotic mice. Although developing normally, adult transgenic mice exhibited a slight form of graft-versus-host (GVH)-like disease characterized by many morphological abnormalities occurring locally in the spleen, testis, lung and liver. In addition, the percentage of alphabetaT cells in the spleen was respectively decreased approximately by 32 % and 24 % in two independent transgenic lines, relative to wild-type mice. Conclusion: Ubiquitous expression of Fas ligand can lead to slight GVH-like disease